The role of quorum sensing on copA and copB activity in virulence plasmid replication in Yersinia pseudotuberculosis - Kirby, Jordan (2022)
Replication of the type three secretion pYV virulence plasmid is tightly controlled in Yersinia pseudotuberculosis through the activity of its two repressors copA and copB. Although the functionality and action of these genes have been well studied, the systems governing their activity have yet to be established. Previous observations suggested that a Y. pseudotuberculosis quorum sensing deficient mutant lost its virulence plasmid more rapidly than its parental counterpart. To examine if there was a regulatory relationship between the quorum sensing system and plasmid replication two bioluminescent lux-based promoter fusions were constructed to measure the activity of copA and copB. These reporter plasmids were then cloned into three strains, a Y. pseudotuberculosis parent and two quorum sensing mutants, one deficient in the N-acyl homoserine lactone synthases ytbI and ypsI and the other in the transcriptional regulators ytbR and ypsR. Promoter activity was determined as a measure of bioluminescence and cell density and copA activity was found to be greatly reduced at 26oC and 37oC when compared to the parent and ytbR/ypsR mutant. It was also evident that activity of copA at host temperatures was highest during the early stages of growth to 3 hours and then fell steadily through the later stages of growth. Similar activity was seen at 26oC although the latent activity remained higher when compared to 37oC. In contrast, copB activity was independent of the quorum sensing system with activity being identical in all three strains. copB activity was however found to be dependent on temperature, with the activity of copB being at its highest during later stages of growth at host temperatures and was inactive at 26oC. These data provide evidence that temperature and the quorum sensing system play a role in plasmid replication in Y. pseudotuberculosis.